Applications of In–Fiber Acousto–Optic Devices - Cuadrado-Laborde, C.; Díez, A.; Andrés, M. V.; Cruz, J. L.; Bello-Jimenez, M.; Villegas, I. L.; Martínez-Gámez, A.; Barmenkov, Y. O. (IntechOpen, 2011)
None